1997
DOI: 10.1002/(sici)1096-9063(199707)50:3<211::aid-ps582>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Atrazine Contamination in Soil and Liquid Systems Using Bioaugmentation

Abstract: : Reported levels of atrazine in soils at pesticide mix-load sites can vary between 7É9 ] 10~5 mM and 1É9 mM. We report on a mixed microbial culture, capable of degrading concentrations of atrazine in excess of 1É9 mM. At initial concentrations of 0É046 M and 0É23 M, the mixed population degraded 78% and 21% of atrazine in soil (100 days), respectively. At the same initial concentrations in liquid cultures, 90% and 56% of the atrazine was degraded (80 days), respectively. Decreased degradation in soil samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 30 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…The two atrazine addition levels were selected according to the range of contamination levels in soil (0.017 mg kg À1 -482.7 mg kg À1 ) reported by Grigg et al (1997) as well as its limited phyto-availability because only the roots penetrating through the mesh would be exposed to atrazine in the side-arm compartment. Four replicate pots of each treatment were set up.…”
Section: Experimental Designmentioning
confidence: 99%
“…The two atrazine addition levels were selected according to the range of contamination levels in soil (0.017 mg kg À1 -482.7 mg kg À1 ) reported by Grigg et al (1997) as well as its limited phyto-availability because only the roots penetrating through the mesh would be exposed to atrazine in the side-arm compartment. Four replicate pots of each treatment were set up.…”
Section: Experimental Designmentioning
confidence: 99%
“…Therefore, it is necessary to investigate the effects of various environmental factors on the growth ability of the tested microorganisms (Pattanasupong et al, 2004). On the other hand, it was found that various materials were used as soil amendments, nutrients, to increase and enhance the degradation potential of xenobiotics such as Yard manure compost (Guo et al, 1991;Cole et al, 1995;Gan et al, 1996;Zheng and Cooper, 1996;Vogel, 1996;Grigg et al, 1997;Leoni et al, 1997), biogas slurry and compost (Kadian et al, 2008;Belal et al, 2008). However, after remediation toxicity assessments are needed.…”
Section: Introductionmentioning
confidence: 99%
“…This is important since, to date, pure strains able to mineralize a pesticide have been reported only for a few pesticide compounds. Moreover, bioaugmentation using lab‐cultured pollutant‐degrading isolates often had limited success (Chatterjee et al , 1982; Grigg et al , 1997; Struthers et al , 1998; Topp, 2001; Mertens et al , 2006; Moran et al , 2006; Singh et al , 2006; Bazot & Lebeau, 2008). On the other hand, the few reports on bioaugmentation of contaminated matrices with pollutant‐primed materials showed promising results (Barbeau et al , 1997; Runes et al , 2001; Grundmann et al , 2007).…”
Section: Introductionmentioning
confidence: 99%